Reflection of “O Nga: Laa” Value behind Capital Accounting Practices by Farmers - Thalib, Mohamad Anwar; Suaib, Rafka; Edis, Edis (AKTIVA: Journal Of Accountancy and Management, 2024)
Purpose: This study aims to reveal capital accounting implemented by rice farmers based on local cultural values. Design/methodology/approach: This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy.Research Findings: The study results show that farmers implement four capital accounting: capital sourced from debt, from side business income, capital used to finance agricultural needs, and capital used to share, among others. The practice of capital accounting is conditional on family (“O nga: laa”) value. It is reflected through the actions of farmers who use their crops to fulfill their personal needs and distribute rice free of charge to their neighbors. This is so the farmers’ neighbors can also feel happiness when the harvest season arrives. In the Islamic culture of the people of Gorontalo, the value of “O nga: laa” is often internalized by the elders through the expression (lumadu) “diila bo ilaato binthe wawu pale.” This expression contains the meaning of a family statement because of blood relations or family ties.Contribution/Originality/Novelty: The results of this study provide implications for the existence of the concept of capital accounting by farmers with local cultural values. Tujuan Penelitian: Penelitian ini bertujuan untuk mengungkapkan akuntansi modal yang dipraktikkan oleh petani padi berdasarkan nilai budaya lokal.Desain / metodologi / pendekatan: Kajian ini menggunakan paradigma Islam dengan pendekatan etnometodologi Islam. Ada lima tahapan analisis data yaitu amal, ilmu, iman, informasi wahyu, dan ihsan.Temuan Penelitian: Hasil kajian menunjukkan bahwa petani menerapkan empat praktik akuntansi modal, yaitu modal yang bersumber dari hutang, dari pendapatan usaha sampingan, modal yang digunakan untuk membiayai kebutuhan pertanian, dan modal yang digunakan untuk berbagi, dengan sesama. Praktik akuntansi modal syarat dengan nilai kekeluargaan (“O nga: laa”). Hal itu tercermin dari tindakan para petani yang menggunakan hasil panennya untuk memenuhi kebutuhan pribadi dan membagikan beras secara cuma-cuma kepada tetangganya. Hal ini agar tetangga petani juga bisa merasakan kebahagiaan saat musim panen tiba. Dalam budaya Islam masyarakat Gorontalo, nilai “O nga:laa” sering diinternalisasikan oleh para tua-tua melalui ungkapan (lumadu) “diila bo ilaato binthe wawu pale” Ungkapan ini mengandung makna pernyataan kekeluargaan karena adanya hubungan darah atau ikatan keluarga.Kontribusi / Orisinalitas / Kebaruan: penelitian ini memberikan kontribusi tentang hadirnya konsep akuntansi modal oleh para petani berbasis nilai budaya lokal.